Consolidação do direito à moradia através da regularização fundiária urbana de interesse social e à luz da lei nº 13.465/17 - Ferreira, Milena Santos (Universidade Federal Rural do Semi-Árido, 2017)
The study aims at the importance of land regularization of social interest and its proceedings with legal institutions that focus on the effectiveness of the right to adequate housing. It is important to realize that this specific regularization involves the issue of social exclusion, as it is turned to people who lack basic human rights. It is generally known, not only among legal experts, that housing is the first step to promote citizenship, a step which allows the development and appropriation of concrete results of an acknowledged and effective right, which leads to the importance of its scientific research concerning the effectiveness of the right to adequate housing. The research targets to evaluate whether the application of land regularization of social interest has promoted consolidation to adequate housing, as an alternative path mainly to housing loans impelled by the Federal Government, to examine the reasons why the procedural regime of the Law nº 11.977/09 has been altered and the benefits or disadvantages that this derogation, by the Law nº 13.465/17 (conversion of the interim measure nº 759/16), has brought to the legal order and social context. For that, were followed the methods of inductive and dialectical approach, the methods of historical and comparative procedure and the quantitative and qualitative methodology. Initially, historical information on property rights will be exposed; afterwards, some considerations regarding housing as social demand, as well as the effects of the application of the previous regimen of land regularization and the motivation presented by the Executive Power to suspend its usage by means of an interim measure. Only then will it be possible to deduce, with the conceptual support of Steven Croley's reviewed theory of public choice that, unlike the propaganda against the new legal framework, carried out by some social movements, the mentioned alterations to the procedure presented reveal their improvement – due to the modernization of legal institutes, the filling of existing gaps, the exclusion of bureaucratic obstacles supported by mere formalities, among other reasons. It‟s possible to conclude that the land regularization of social interest, in light of the Law nº 13.465/17, presents a positive prognostic regarding the effectiveness of the right to housing.
Artigo Acadêmico
Keywords: Regularização fundiária de interesse social; Direito social à moradia digna; Legitimação de posse; Doação de propriedade; Land regularization of social interest; Right to adequate housing; Legitimation of possession; Property donation; CIENCIAS SOCIAIS APLICADAS::DIREITO